Effects of polymorphism in the bovine PTPRQ gene on the expression of MYF6 and MYF5 genes in skeletal muscle and on meat production traits in beef bulls - D. Robakowska-Hyżorek; R.R. Starzyński; B. Żelazowska; J. Oprządek; T. Sadkowski; L. Zwierzchowski (Czech Journal of Animal Science, 2016)
The aim of the study was to characterize nucleotide sequence polymorphisms in the bovine PTPRQ gene, to search for their possible effect on the expression of myogenic factor 6 (MYF6; MRF4) and myogenic factor 5 (MYF5) genes in skeletal muscle and on meat production traits. Three novel SNPs were found in intron 35 of the bovine PTPRQ gene: g.200,451A>G, g.200,467T>C, g.200,480C>T (GenBank Acc. No. NW_001494990.2; counted from translation initiation site). These SNPs are placed very closely to each other (within 29 base pairs). The results showed that genotype influenced the expression of MYF6 and MYF5 genes in longissimus dorsi muscle of Limousine bulls both at the transcript and protein levels. Moreover, an association was found between the PTPRQ genotype and carcass traits in Limousine bulls. These findings suggest that bovine PTPRQ gene may contain regulatory sequences for MRF genes located 24 kb downstream. The results also showed that nucleotide sequence polymorphisms in the PTPRQ gene may influence meat production traits in beef cattle, possibly through the regulation of the MRF genes expression.